2020
DOI: 10.1177/0890117119898613
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Well-Being Factors That Predict Employee Participation, Health and Medical Cost Impact, and Perceived Support

Abstract: Purpose: This study tested relationships between health and well-being best practices and 3 types of outcomes. Design: A cross-sectional design used data from the HERO Scorecard Benchmark Database. Setting: Data were voluntarily provided by employers who submitted web-based survey responses. Sample: Analyses were limited to 812 organizations that completed the HERO Scorecard between January 12, 2015 and October 2, 2017. Measures: Independent variables included organizational and leadership support, program com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…This study suggests that upper management support was integral to successful implementation of HP programming, and the sites without management support were unable to proceed. These findings correspond with a study evaluating best practices in workplace health promotion that reviewed wellness programs in 812 organizations, and identified organizational and leadership support practices as essential factors to participation as well as health and medical cost impact [ 43 ]. Similarly, a recent study found that workers are more likely to both participate in WHP and engage in recommended health behaviors when they feel that their employers care about their health [ 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…This study suggests that upper management support was integral to successful implementation of HP programming, and the sites without management support were unable to proceed. These findings correspond with a study evaluating best practices in workplace health promotion that reviewed wellness programs in 812 organizations, and identified organizational and leadership support practices as essential factors to participation as well as health and medical cost impact [ 43 ]. Similarly, a recent study found that workers are more likely to both participate in WHP and engage in recommended health behaviors when they feel that their employers care about their health [ 44 ].…”
Section: Discussionsupporting
confidence: 85%
“… 25 These items were divided into nine categories: leadership, relevance, partnership, comprehensiveness, implementation, engagement, communication, data driven, and compliance. A previous study 26 used HERO scorecard data to examine factors in health promotion programs affecting participation in health assessments and biometric screening, the impact on medical costs, and perceptions of organizational and leadership support. That study found that organizational and leadership support was the strongest predictor of success in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Jessica Grossmeier, PhD, MPH, Patricia H. Castle, PhD, Jennifer S. Pitts, PhD, Colleen Saringer, PhD, Kristi Rahrig Jenkins, PhD, Mary T. Imboden, PhD, David J. Mangen, PhD, Sara S. Johnson, PhD, Steven P. Noeldner, PhD, MS, Shawn T. Mason, PhD, LP. 7…”
Section: Editors’ Picks Papers Of the Year For 2020 (Volume 34)mentioning
confidence: 99%